The ameliorative effect of chrysin on ovarian toxicity caused by methidathion in female rats - Hamed, Amany M.; Ali, Fatma Abo Zakaib; Mohammed, Ard elshifa M. E.; Alrasheedi, Muneera; Ragab, Islam; Aldoghaim, Maryam; Soliman, Safaa S. (Frontiers in Molecular Biosciences, 2024)
Introduction: Methidathion (MD) is commonly used in agriculture and has adverse effects on reproduction. Chrysin (CHR) has several advantageous properties, such as anti-inflammatory, anti-cancer, and antioxidant properties. The purpose of the current investigation was to assess CHR’s therapeutic efficacy in reducing ovarian toxicity brought on by MD.Methods: Twenty-four female rats were divided into four groups of six animals each. Group 1 served as a control, while group 2 rats received MD (5 mg/kg). Rats in Group 3 received CHR at a dose of 50 mg/kg. Rats in group 4 received treatment with CHR after MD intoxication.Results and Discussion: Our research revealed that MD significantly (p < 0.001) increased the levels of MDA, caspase-3, FSH, LH, CA-125, and TNF-α but significantly (p < 0.001) decreased the levels of SOD, GSH, E2, and progesterone when compared to the control and CHR groups. After receiving CHR therapy, damage induced by MD was significantly (p < 0.001) repaired.Conclusion: This study showed that CHR could mitigate the adverse effects that MD causes to the ovaries by decreasing oxidative stress, inflammation, and apoptosis; improving antioxidant status; and restoring the correct ratio of sex hormones.